Safety, pharmacokinetics, and antiviral effects of ABI-H0731, a hepatitis B virus core inhibitor: a randomised, placebo-controlled phase 1 trial. (February 2020) - Yuen, Man-Fung; Agarwal, Kosh; Gane, Edward J; Schwabe, Christian; Ahn, Sang Hoon; Kim, Dong Joon; Lim, Young-Suk; Cheng, Wendy; Sievert, William; Visvanathan, Kumar; Ruby, Eric; Liaw, Sandy; et al.
Summary: Background: Therapies with novel mechanisms of action against hepatitis B virus (HBV) infection are being explored with the goal of achieving a functional cure (sustained off-treatment response) without requiring lifelong therapy. We aimed to evaluate the pharmacokinetics, safety, and antiviral activity of ABI-H0731, an investigational inhibitor of the HBV core protein. Methods: This phase 1, randomised, placebo-controlled study was done in two parts. In part 1, healthy adults without hepatitis B aged 18–65 years at one clinical research centre in New Zealand (eight participants per dose cohort) were randomly assigned (3:1) to receive single oral doses of ABI-H0731 (100, 300, 600, or 1000 mg) or matching placebo, or once-daily or twice-daily doses of ABI-H0731 800 mg or matching placebo for 7 days. In part 2, adults aged 18–65 years at clinical research centres in New Zealand, Australia, the UK, Hong Kong, Taiwan, and South Korea with chronic HBV (12 participants per dose cohort) were randomly assigned (5:1) to receive ABI-H0731 (100, 200, 300, or 400 mg) or matching placebo once daily for 28 days. In part 2, participants were required to have HBeAg-positive or HBeAg-negative chronic HBV infection, with serum HBV DNA concentrations of at least 2 × 10 4 IU/mL (HBeAg-positive) or 2 × 10 3 IU/mL (HBeAg-negative) and serum alanine aminotransferase concentrations less than seven times the upper limit of normal. Both parts used simple randomisation, with study participants, site personnel, and study monitors masked to treatment assignments. The primary study objective was dose-related safety and tolerability of ABI-H0731 in healthy volunteers and in participants with chronic HBV infection, assessed in all treated participants. Key secondary assessments included pharmacokinetic analyses and virological responses. This study is registered with ClinicalTrials.gov, identifier NCT02908191 and is completed. Findings: 48 [61%] of 79 healthy volunteers were enrolled in the single-ascending or multiple-ascending dose phase of part 1 between Nov 16, 2016, and Jan, 27, 2017. 38 [55%] of 69 HBV-infected participants were enrolled in part 2 between June 15, 2017, and March 15, 2018. All adverse events were non-specific and of mild or moderate intensity apart from a single HBV-infected participant given the 400 mg dose who developed a severe (grade 3) maculopapular rash and terminated treatment. Overall, the most frequent adverse events of any grade among the 74 participants who received ABI-H0731 were headache (11 [15%]), influenza-like illness (seven [9%]), and dizziness (six [8%]); the most frequent adverse events considered treatment-related were rash (four [5%]) and dizziness (three [4%]). In part 1, ABI-H0731 reached maximum plasma concentrations (Tmax ) in 2·50–4·17 h; the mean plasma half-life (t1/2 ) was 23·5–28·4 h. In part 2, mean maximum HBV DNA declines from baseline were 1·7 log10 IU/mL in the 100 mg dose cohort, 2·1 log10 IU/mL in the 200 mg dose cohort, and 2·8 log10 IU/mL in the 300 mg dose cohort. Across dose cohorts, serum HBV RNA declines correlated with HBV DNA declines. Interpretation: No pattern of treatment-emergent adverse events was observed at ABI-H0731 doses up to 300 mg in individuals with chronic hepatitis B. ABI-H0731 was rapidly absorbed and exhibited a plasma half-life supportive of once-daily dosing. Dose-dependent decreases in serum HBV DNA and RNA concentrations are consistent with the proposed mechanism of action. Funding: Assembly Biosciences.